Credit intermediation and the transmission of macro-financial uncertainty: International evidence - Martin Gächter; Martin Geiger; Sebastian Stöckl (Liechtenstein Institute, 2019)
We examine the transmission of global macro-financial uncertainty to economic activity depending on the current state of the banking sector. Previous literature suggests that credit supply and uncertainty shocks are important drivers of economic activity, but the distinction between the two is empirically challenging. In this paper, we introduce a new, but surprisingly simple measure of macro-financial uncertainty at the global level while the state of credit intermediation is being captured on the country level. Macro-financial uncertainty generally exerts adverse effects on economic growth in a sample of advanced economies. We find, however, that a shock to uncertainty is strongly reinforced when credit intermediation is distressed. In addition, we show that both macroeconomic and financial market uncertainty are associated with lower economic activity, although the latter exerts stronger effects. State-dependency of the effects is prevalent in both cases. Our findings have important policy implications, highlighting both the state of the banking sector as well as the origin of uncertainty as crucial factors in the transmission of uncertainty.
Keywords: D80; E32; E44; G21; 330; uncertainty; credit intermediation; local projection method; state-dependency